A story of Islamic art - Milwright, Marcus, author.
1 online resource
Keywords: Providing an introduction to the artistic and architectural traditions of the Islamic world, A Story of Islamic Art explores fifty case studies, taken from different regions of the Islamic world and from the seventh to the twenty-first centuries. The novel aspect of these case studies is that they are presented as fictional narratives, allowing the reader to imagine art and architecture, either in their original cultural settings or at some later point in their histories. These stories are supported by a scholarly framework that allows the reader to continue their exploration of the chosen artefacts and their historical context. The fifty case studies take the form of short stories, each of which focuses on one or more object from the Islamic world. These encompass portable items in a wide variety of media, book illustrations, calligraphy, photographs, architectural decoration, buildings, and archaeological sites. The book also provides a detailed introduction, maps, timeline, glossary, and guides for further reading. This book offers accessible answers to key questions in the scholarship on Islamic art and architecture from its earliest times to the present. The issues dealt with in each of the stories include iconography, attitudes towards representation, the role of script, the elaboration of geometric decoration, the creation of sacred and secular spaces in architecture, and the socio-cultural context of art production and consumption. Artistic interactions between the Islamic world and other regions including Europe and China are also discussed in this book. A Story of Islamic Art isan engaging and informativeintroduction for interested readers and students of Islamic art, history, and architecture.